MOTIVATION THROUGH ISLAMIC AND PSYCHOLOGICAL LENSES: ALIGNMENTS AND CONTRASTS - Rayhani, A.; Ramli, M. (Journal on Research and Review of Educational Innovation, 2024)
Motivation is the driving force that propels individuals to achieve specific goals. In psychology, motivation is often linked to the fulfillment of basic needs, as described by Abraham Maslow in his hierarchy of needs. Motivation can emerge internally, such as personal desires and beliefs, or externally, such as environmental rewards. Meanwhile, in Islam, motivation is grounded in sincere intentions (niyyah) and oriented toward the afterlife. Islam emphasizes good deeds, sincerity, and reliance on God (tawakal) as primary drivers of human behavior. This journal compares the perspectives of Islam and psychology in understanding the concept of motivation. The study reveals that Islamic motivation focuses on seeking God's pleasure and eternal well-being in the afterlife, whereas psychology emphasizes worldly needs and self-actualization. Despite their differences, both approaches highlight the importance of motivation in shaping behavior and enhancing individuals' holistic well-being.